Unexpected Routes of the Mutagenic Tautomerization of the T Nucleobase in the Classical A·T DNA Base Pairs: A QM/QTAIM Comprehensive View - Brovarets', Ol'ha O.; Tsiupa, Kostiantyn S.; Dinets, Andrii; Hovorun, Dmytro M. (Frontiers in Chemistry, 2018)
In this paper using quantum-mechanical (QM) calculations in combination with Bader's quantum theory of “Atoms in Molecules” (QTAIM) in the continuum with ε = 1, we have theoretically demonstrated for the first time that revealed recently highly-energetic conformers of the classical A·T DNA base pairs – Watson-Crick [A·T(wWC)], reverse Watson-Crick [A·T(wrWC)], Hoogsteen [A·T(wH)] and reverse Hoogsteen [A·T(wrH)] – act as intermediates of the intrapair mutagenic tautomerization of the T nucleobase owing to the novel tautomerisation pathways: A·T(wWC)↔A·T*(w⊥WC); A·T(wrWC)↔A·TO2*(w⊥rWC); A·T(wH)↔A·T*(w⊥H); A·T(wrH)↔A·TO2*(w⊥rH). All of them occur via the transition states as tight ion pairs (A+, protonated by the N6H2 amino group)·(T−, deprotonated by the N3H group) with quasi-orthogonal geometry, which are stabilized by the participation of the strong (A)N6+H···O4−/O2−(T) and (A)N6+H···N3−(T) H-bonds. Established tautomerizations proceed through a two-step mechanism of the protons moving in the opposite directions along the intermolecular H-bonds. Initially, proton moves from the N3H imino group of T to the N6H2 amino group of A and then subsequently from the protonated N6+H3 amino group of A to the O4/O2 oxygen atom of T, leading to the products – A·T*(w⊥WC), A·TO2*(w⊥rWC), A·T*(w⊥H), and A·TO2*(w⊥rH), which are substantially non-planar, conformationally-labile complexes. These mispairs are stabilized by the participation of the (A)N6H/N6H'···N3(T) and (T)O2H/O4H···N6(A) H-bonds, for which the pyramidalized amino group of A is their donor and acceptor. The Gibbs free energy of activation of these mutagenic tautomerizations lies in the range of 27.8–29.8 kcal·mol−1 at T = 298.15 K in the continuum with ε = 1.